Covering the Real Reason for the Financial Crises 2008 All over theWorld – The Iraq War 2003, Based on the Momtchil Dobrev’s “Theory of Generate of Crises” and the Momtchil Dobrev’s “Theoryof the Mafia” (Asian Business Research, 2017)
In this paper is described the explanation of the real reasons for the financial crises 2008 all over the world based on the Lord Prof PhD PhD Momtchil Dobrev-Halachev developed 2008 “Theory of generating of crises “ and 2001 “ Theory of the mafia”. Based on these two theories, this paper explains the establishment of the financial crises2008 all over the world (Dobrev, 2015).